P 108 Modified motor threshold criterion for intraoperative corticobulbar MEPs for prediction of postoperative facial nerve outcome. Issue 10 (October 2017) - Szelenyi, A.; Wang, L.; Greve, T.; Rachinger, W.; Tonn, J.; Schichor, C.
Abstract : Background: Intraoperatively, facial nerve (FN) function can be assessed with corticobulbar Motor Evoked Potentials (FN-coMEP). MEP-amplitude decrement and increase in motor threshold (MT) serve as warning criteria. A novel threshold criterion for extremity MEP additionally compared MT-increments to the non-operated side (bilateral final-to-baseline motor threshold level, BFB-MT). We applied BFB-MT for FN-coMEP with regard to postoperative FN-function. Methods: 47 consecutive patients (26f; 46 ± 18 yrs) undergoing posterior fossa tumor surgery (40 cerebellar pontine angle; 6 petroclival, 1 foramen magnum) were analyzed. FN-coMEP were elicited with anodal transcranial electric stimulation at C4; C3 referenced to Cz, and recorded from bilateral orbicularis oris and mentalis muscles. Preoperative and one day (1d), one week (1w) and 3 month (3m) postoperative House-Brackmann FN-function scores were compared and deterioration was classified as mild (increase ⩽1) or marked (increase ⩾2). BFB-MT difference of >20% (operated vs. non-operated side) was regarded as significant. Increase of MT on the operated side of ⩾20 mA served as reference criterion (RefC). The predictive value was analyzed and compared by χ 2 test, nonparametric Spearman correlation, and Logistic regression analysis. Results: At 1d, 15% of the patients (7/47) showed mild HB deterioration, 36% (17/47) marked. At 1w, 12 patients showed mild deterioration (25%), 10 marked (19%). 3 m follow-up in 40 patients (85%) showed recovery in 31 patients (78%). 5 patients (13%) showed mild and 4 (10%) marked deterioration (all in giant or recurrent tumor). The overall technical success rates of FN-coMEP on the operated and non-operated side of the tumor were 93.6% and 87.2%. For the 21 patients with stable FN outcomes, the mean final-to-baseline threshold increment on operated side was 6.7 ± 4.6 mA compared to 2.8 ± 3.4 mA ( p  = 0.005) on the contralateral side. In 23 patients enduring postoperative deterioration of FN function, mean BFB-MT threshold increment on operated side was 24.1 ± 18.6 mA, compared to 9.2 ± 9.7 mA ( p  = 0.001) on the non-operated side. A significant statistical difference also existed in the threshold increment between these two subgroups ( p ). Conclusion: BFB-MT serves as better indicator for postoperative FN function than the RefC. Further, it was identified as a variable for postoperative FN-function at 1w and seems to be a useful method for predicting the postoperative facial function. Such, FN-coMEP are feasible as a routine method for intraoperative FN monitoring and might help to tailor warning criteria.